On the use of orientation filters for 3D reconstruction in event-driven stereo vision - Camunas-Mesa, Luis Alejandro; Serrano-Gotarredona, Teresa; Ieng, Sio Hoi; Benosman, Ryad B.; Linares-Barranco, Bernabe (Frontiers in Neuroscience, 2014)
The recently developed Dynamic Vision Sensors (DVS) sense visual information asynchronously and code it into trains of events with sub-micro second temporal resolution. This high temporal precision makes the output of these sensors especially suited for dynamic 3D visual reconstruction, by matching corresponding events generated by two different sensors in a stereo setup. This paper explores the use of Gabor filters to extract information about the orientation of the object edges that produce the events, therefore increasing the number of restrictions applied to the matching algorithm. This strategy provides a larger number of pairs of matching events, improving the final 3D reconstruction.